1991
DOI: 10.1007/bf00194629
|View full text |Cite
|
Sign up to set email alerts
|

Gene deletions causing human genetic disease: mechanisms of mutagenesis and the role of the local DNA sequence environment

Abstract: Reports describing short (less than 20 bp) gene deletions causing human genetic disease were collated in order to study underlying causative mechanisms. Deletion breakpoint junction regions were found to be non-random both at the nucleotide and dinucleotide sequence levels, an observation consistent with an endogenous sequence-directed mechanism of mutagenesis. Direct repeats of between 2bp and 8bp were found in the immediate vicinity of all but one of the 60 deletions analysed. Direct repeats are a feature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
294
1
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 439 publications
(320 citation statements)
references
References 115 publications
(78 reference statements)
24
294
1
1
Order By: Relevance
“…34 The independent origin of the 4bp deletions might be caused by slippage effects during replication. 38,39 Missense mutations in the BRCA genes Most mutations reported in the BIC database are small deletions, small insertions and nonsense mutations, all predicted to cause premature termination of translation and thus are considered as predisposing. In the absence of functional tests for the BRCA1 and BRCA2 proteins, most missense mutations, in frame deletions, or certain intronic substitutions pose serious problems for the interpretation of their effects on tumorigenesis.…”
Section: Most Recurrent Mutations Are Founder Mutationsmentioning
confidence: 99%
“…34 The independent origin of the 4bp deletions might be caused by slippage effects during replication. 38,39 Missense mutations in the BRCA genes Most mutations reported in the BIC database are small deletions, small insertions and nonsense mutations, all predicted to cause premature termination of translation and thus are considered as predisposing. In the absence of functional tests for the BRCA1 and BRCA2 proteins, most missense mutations, in frame deletions, or certain intronic substitutions pose serious problems for the interpretation of their effects on tumorigenesis.…”
Section: Most Recurrent Mutations Are Founder Mutationsmentioning
confidence: 99%
“…Human gene mutations appear to be caused by multiple mechanisms whose relative importance is probably governed by local primary and secondary DNA structure. 7 We have searched for consensus sequences located in the immediate vicinity of gene mutations and for "hot spots" that mediate illegitimate recombinations, a mechanism that is suggested to be crucial for the generation of genomic instability and cancer. …”
mentioning
confidence: 99%
“…Among these mutations, Bassett et al (1998) reported hot spots for small deletions and insertions in exons 2, 3, and 10. The mutations identified in the present study are also located at exons 2 and 3, where misalignment of the dinucleotide repeat during replication could easily be expected from the nucleotide sequence of this region (Krawczak and Cooper 1991). Irrespective of these mutational hot spots, the mutation sites are fundamentally distributed over the entire exon.…”
Section: Discussionmentioning
confidence: 60%